La détermination en polonais: un déterminant zéro ? - Muryn, Teresa (Neophilologica, 2010)
In the intensional theory of article proposed by Stanisław Karolak, the article is a symbol which plays a reflexive function rather than a semantic one in the structure of a noun phrase. It reflects the intensional values of phrases placed in the syntactic positions opened by other elements. Various languages may develop different rules of selecting the reflexive symbols of definiteness in noun phrases which are equivalent and intensionnally identical across languages. The aim of this article is to verify if the intensional theory could explain the absence of formal exponents of definiteness / indefiniteness in Polish.